"Quick and to the point": Participant Input for the Development of an Online Gardening Intervention to Improve Cardiovascular Health. (14th June 2022) - Veldheer, Susan; Whitehead-Zimmers, Maxfield; Watt, Benjamin; Sciamanna, Christopher; Bordner, Candace
Abstract: Objectives: Gardening is associated with cardiovascular health promoting behaviors such fruit and vegetable (F&V) intake and physical activity. The majority of published gardening interventions are based on labor intensive, in-person models and there is little published data on optimal delivery modes or topics needed to develop a scalable, online intervention. The purpose of this study was to solicit input from a pool of potential online learners to inform the development of an online gardening intervention. Methods: A survey was delivered to an Amazon Mechanical Turk (mTurk) panel including quantitative and open-ended questions. Participants were asked about socio-demographic and health information, their experiences with gardening, preferences for intervention delivery (e.g., in person or online), and topics needed to teach new gardeners. Quantitative data were summarized with chi-squared tests or t-tests and comparisons were made between participants with 0 years (Never gardeners, NG) and 1+ years (Experienced Gardeners, EG). Qualitative data were coded and organized into intervention functions based on the Behavior Change Wheel from Michie et al. Results: Overall, 465 participants were included (45.6% NG and 54.4% EG). Participants had a mean age of 40.2 years, were majority white (79.8%), lived in non-urban areas (56.8%) and had at least one risk factor for cardiovascular disease (73.6%). Gardening program interest was high for both NG and EG (67.0% v. 84.2% respectively, p < 0.001). Both groups preferred "quick and to the point" delivery methods including <5 minute videos (64.2% NG, 57.7% EG, p = 0.191). Key intervention functions identified were education and training (fundamentals of gardening maintenance at each step for planting, harvesting, and cooking), environmental restructuring (social support), persuasion (the benefits of gardening), modeling (seeing others who were successful), and enablement (the provision of supplies and tools). Conclusions: Participants in this sample were interested in learning gardening skills, preferred "quick" online intervention delivery methods, and were interested in a multi-component intervention including how to garden from planting to harvesting and cooking. Funding Sources: This study was funded by the Penn State Department of Professional Development (PI: Veldheer).